2014
DOI: 10.2478/sjph-2014-0018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of self-rated health – information on patients’ unmet needs?

Abstract: Ključne besede: samoocena zdravja, družinska medicina, tveganje za srčno-žilne bolezni

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…Randomised trials of patients with metabolic syndrome showed that an improved lifestyle with a healthy diet and regular physical activity improved HRQoL (34)(35) and self-rated health (36). The results of Imayama on postmenopausal women showed the same (37).…”
Section: Discussionsupporting
confidence: 62%
“…Randomised trials of patients with metabolic syndrome showed that an improved lifestyle with a healthy diet and regular physical activity improved HRQoL (34)(35) and self-rated health (36). The results of Imayama on postmenopausal women showed the same (37).…”
Section: Discussionsupporting
confidence: 62%
“…In testing lifestyle characteristics, we found a weak bivariate correlation of HRQoL with a healthy diet and a significant association with physical activity in the multivariate model. Randomised trials of patients with metabolic syndrome showed that an improved lifestyle with a healthy diet and regular physical activity improved HRQoL ( 34 , 35 ) and self-rated health ( 36 ). The results of Imayama on postmenopausal women showed the same ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most widely used are single-item indicators that differ in the number of available answers, but, in general, they represent a parallel assessment of subjective health ( 10 ). A study in Slovenia using SRH showed that PSRH is associated with multimorbidity and unhealthy life-style ( 17 ). Subjective evaluation of health is used also in econometric analyses and health technology assessment ( 18 ).…”
Section: Introductionmentioning
confidence: 99%